Effect of N fertilizer and N use efficiency under different N levels of application in high-fertility paddy field - FENG Tao; YANG Jing-ping; SHI Hong-xin; ZHENG Hong-fu; SUN Jun-hua (浙江大学学报. 农业与生命科学版, 2006)
In this paper the effect of N fertilizer and N use efficiency under different levels of N application in high-fertility paddy field in Northern Zhejiang Province was studied. The results showed that rice yield and N content of leakage water and paddy soil were greatly influenced by the amount of N fertilizer. The yield showed no significant variation when the applied nitrogen were within the range of 150-225 kg·hm-2. N content of leakage water and soil increased quickly with the N application up to 225 kg·hm-2, it would lead to severe non-pointing source pollution of N. The result indicated that N use efficiency was so low that uptake of N by rice efficiency was only 21.55% in average. Agronomic and physiological efficiency of N were only 7 kg·kg-1 and 20 kg·kg-1, which were far below the average level of the whole nation. Considering the N use efficiency and theory of marginal profit analysis, the 140-200 kg·hm-2 could be a reasonable range of nitrogen application for the high-yielding paddy field in northern Zhejiang Province.